Development of Weluan Beach Tourism Object in Olilit Raya Village, South Tanimbar District, Tanimbar Islands Regency - Kadung, Gerardus; Lasaiba, Mohammad Amin; Sihasale, Daniel Anthoni (Program Studi Pendidikan Geografi FKIP Universitas Pattimura, 2023)
Tourism development is the key to regional growth, driving the economy and increasing foreign exchange earnings. Increased visits, growth of tourism businesses, and contribution of foreign exchange earnings are evidence of the effectiveness of the tourism sector in Maluku. Challenges such as conflicts of interest and obstacles to infrastructure development are obstacles. Efforts to develop tourism in Maluku must be carried out sustainably, involving the private sector and the community. It encourages tourism as the central pillar of regional development, improves community welfare, and positively contributes to local and national economic growth. The main objective of this study is to conduct an in-depth analysis and provide management recommendations related to the development of the Weluan Beach tourist attraction in Olilit Raya Village, Tanimbar Islands Regency. The methods used are observation and interviews, and the data is formulated into a SWOT analysis. The results of this study are based on the table and internal and external factors at Weluan Beach show values ​​of 0.53 and 2. Strategic recommendations must be by the SWOT quadrant, strengthening strengths by utilizing opportunities. The strategy involves the tourism office, lodging, restaurants, travel agents, and the community. Increase promotion with social media, cross-sector coordination, and improve the quality of facilities and infrastructure. Support from the village government and local investors, management innovation by adding attractions and regular events, active community participation in promotion and maintaining cleanliness, and between the government, tourism actors, and the community are the keys to the success of Weluan Beach as a superior destination.